INTERDISCIPLINARY FUTURE SCENARIO WITH 100PROSIM: FEWER ANIMAL FOODS PROVIDE SPACE FOR RENEWABLE ENERGY (Proceedings of the International Conference on Agriculture, 2022)
The climate crisis combines land scarcity, high meat consumption, grubbing-up and environmental disasters. Agriculture needs land to ensure food security. In addition, much forestland is needed to store the greenhouse gas carbon dioxide. Access to cleaner energy sources and technologies also helps mitigate the climate crisis and the efficiency of wind- and solar-energy-infrastructures is recognized. These energy sources also require land. This raises the question of how land can be used efficiently to ensure food security, forestland and renewable energy in the context of the climate crisis. Scientific approaches are to save land area from animal husbandry by reducing animal products. Meat production is particularly resource intensive and requires more area than crop products. The project “Future Discourses in Environmental Communication” at Osnabrück University of Applied Sciences addresses different social groups in order to discuss the climate crisis, energy system made of 100% renewable energies and land consumption. For this purpose, targeted workshops are conducted in combination with a simulation tool for 100% renewable energy scenarios. The tool, based on Microsoft Excel, simulates for the participants the potential area for energy production from renewable energies as well as the relationship to energy consumption. The results of the workshops show that participants are increasingly taking up the approach of saving land from animal husbandry by producing and consuming less animal and more vegetable-foods. Consequently, there is enough space for a future based on 100% renewable energy. In general, meat consumption is related to political attitudes. Those who consume less meat are considered more environmentally conscious. The hypothesis could therefore put forward that the participants want to show their climate and energy awareness by criticizing meat consumption.
Keywords: energy sources; renewable energy; climate crisis; animal food; land area